A Sense of Belonging: Walking with Thaer through migration, memories and space. Issue 2 (1st September 2014) - O'Neill, Maggie; Perivolaris, John
'A Sense of Belonging: Walking with Thaer through migration, memories and space' introduces and provides a conceptual and affective context to the photographic essay by John Perivolaris 'Walking with Thaer'. Undertaken as part of the 'Transational Communities: Towards a Sense of Belonging' project funded by the AHRC, Thaer led John on a walk from a space he called home in the city to a special place, mapping the spaces and places along the way that were important to him. The process of walking and talking opened up a relational and dialogic space where embodied knowledge, the relationship between the visual and other senses and memories were shared. The photographs and the narrative help us to see the importance of memories, that the past is 'right here, in the midst of the present' and that the stories told here also 'leap forward' and help to 'map the future'. In looking at the minutiae, what is ordinarily overlooked, we can often reach a better understanding of the bigger picture – towards a radical democratic imaginary.